Pengaruh Pergaulan Sesama Siswa Terhadap Pembinaan Akhlak Siswa Di MTs Darul Arafah Pangkalan Brandan - Zulaikha, Ali Mukhlis Ar, Zaifatur Ridha (Khazanah : Journal of Islamic Studies, 2023)
This study focuses on the discussion of the influence of fellow students' association on the moral development of students at MTs Darul Arafah Pangkalan Brandan. In this study the authors used a type of quantitative research that is associative. Research respondents totaled 78 students. Data processing using Microsoft Office Excel and SPSS applications. The results of the study explained that there was a significant influence between the association of fellow students on the moral development of students at MTs Darul Arafah Pangkalan Brandan. This is obtained through the results of hypothesis testing, namely the test which shows a significance value of 0.00 because the significance value is smaller than 0.05 (0.00 <0.05) and the tcount > ttable (11.737 > 1.99167) then there is the influence of the variable X on Y variable. The association of fellow students that occurred at MTs Darul Arafah Pangkalan Brandan influenced the moral development of students at the school by 64%. There is a positive or parallel relationship between fellow students' association with student moral development, the better the association that occurs among students at MTs Darul Arafah Pangkalan Brandan, the moral development of students at the school will also be better and vice versa, if the association of fellow students at MTs Darul Arafah Pangkalan Brandan is bad, so the moral development of students in the school will also be bad. This shows that the association of fellow students has a close relationship with the development of student morals.